Labour-market in a border-area; searching for jobs and the influence of borders - B. Martin R. van der Velde (European Regional Science Association (ERSA), 1998)
At the moment borders, border-related problems, and the process of tearing down borders are very much in the centre of interest. Especially in Europe a lot of scientific work is done with regard to borders of countries, to determine their role in the ongoing integration process. In this respect border-regions are considered to be able to play a catalytic role. The borderland economies on both sides of a national border in this view have to be changed into one transborder economy. Initiatives to encourage cross-border integration however are not always successful. To our opinion, one of the main reasons lies in the fact that the border has many faces. The effect of a border differs, depending on the type of interaction (e.g. economic, social-cultural or institutional) and the nature of the region it defines. This paper tries to formulate a conceptual framework, within which the different properties of borders and border-regions are taken into account. Next this model is applied to the regional labour-market in the Nijmegen-Arnhem border-area in the eastern part of the Netherlands. The most important questions to be answered are: - Are there effects stemming from the fact the regional labour-market in the Arnhem-Nijmegen is part of a (peripheral) borderland economy? - What are the effects of the border with regard to the interaction of the region Arnhem-Nijmegen with the neighbouring region in Germany? - Is a part of the "natural" labour-market cut off by the national border, or put in other words, what would happen if the Dutch-German border would disappear completely? Keywords: Borders, Regional labour-markets, Transition
Keywords: 330